THE INFLUENCE OF INSTRUCTORS COMPETENCY AND FACILITIES ON THE QUALITY OF EDUCATION AND TRAINING CENTER (ETC) GRADUATES IN FACING THE INDUSTRIAL REVOLUTION 4.0 - Roky Apriansyah; Ziko Fransinatra; Deci Ririen (JURNAL MANAJEMEN DAN BISNIS, 2020)
The industrial revolution 4.0 is a digital-based era that demands the quality of human resources (HR) who have high skills. The Education and Training Center (ETC) is one of the institutions that plays role in increasing the quality level of human resources. This study aims to see the effect simultaneously and partially between the competence of instructors and infrastructure on the quality of ETC graduates in the face of the era of the industrial revolution 4.0. in Indragiri Hulu Regency. The population in this study consists of all ETCs in Indragiri Hulu, there are 15 ETCs and all ETCs were sampled. Multiple regression and correlation analysis using SPSS 22.0 was used to determine whether or not there is an influence and relationship between variables. The results of the study concluded (1) the competence of instructors and infrastructure simultaneously had a significant effect on the quality of graduates. (2) Instructor competence partially has a significant effect on the quality of graduates. (3) Facilities partially has a significant effect on the quality of graduates. The variable that has the greatest contribution to the quality of ETC graduates in Indragiri Hulu Regency is the competence of the instructor followed by infrastructure. In this case, of education it will be very difficult for ETC graduates to compete in the world of work. Because this is a factor caused from within the ETC itself.